Existence and Uniqueness of Abstract Stochastic Fractional-Order Differential Equation - El-Borai, Mahmoud Mohammed Mostafa; S.A., A. Tarek (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
In this paper, the existence and uniqueness about the solution for a class of abstract stochastic fractional-order differential equations where in and are given functions, are investigated, where the fractional derivative is described in Caputo sense. The fractional calculus, stochastic analysis techniques and the standard Picard’s iteration method are used to obtain the required.